THE ROLE OF CITIZENSHIP EDUCATION IN FORMING ACCOUNTANTS WITH INTEGRITY IN THE DIGITAL ERA - Rudyanto Simanjuntak; Pius Deski Manalu (PT. MITRA ANGKASA INFORMATIKA, 2025)
Abstract The digital era brings new challenges to the world of accounting, particularly regarding integrity and professional ethics. Rapid technological developments, such as the automation of financial reporting, the use of cloud-based accounting software, and data analytics, require accountants to be not only technically proficient but also to possess a solid moral foundation. Amidst these digital conveniences, the potential for ethical deviations, data manipulation, and weak accountability has also emerged, a serious concern. In this context, Civics Education (PKn) plays a strategic role in shaping national character and values, which are relevant in producing accountants who are not only competent but also possess high integrity. This study aims to analyze the contribution of Civics courses in shaping the ethical and moral awareness of accounting students in the digital era. Values such as honesty, responsibility, social awareness, and discipline instilled in Civics are key assets in building a culture of professional ethics among students. The research employed a descriptive qualitative method, with data collection techniques including interviews and questionnaires with accounting students from several universities. The research results show that the explicit and implicit integration of civics values into the learning process can increase students' ethical awareness in implementing digital accounting practices. Students with a good understanding of national values show a higher tendency to be honest, accountable, and professional. Therefore, civics needs to be continuously developed as a foundation for accounting students' professional character, both through curriculum strengthening and collaborative approaches across subjects. It is hoped that this collaboration will produce accounting graduates who are not only adaptive to technological developments but also possess strong character and moral responsibility. Keywords: Civic Education, Integrity, Accounting, Digital Era, Professional Ethics